FRACTURES OF THE LOWER THORACIC AND LUMBAR SPINE - Mardonov Jamshid Jahongirovich; Karomov Suhrob Mirmuhsinovich (TADQIQOTLAR, 2025)
ABSTRACT. Fractures of the lower thoracic (T10–T12) and lumbar (L1–L5) spine are common injuries resulting from high-energy trauma, such as road traffic accidents, falls from height, or sports-related incidents. These fractures may involve vertebral body compression, burst fractures, or fracture-dislocations, often accompanied by neurological deficits. Accurate diagnosis, classification, and timely management are essential to prevent long-term disability. This article reviews the epidemiology, mechanisms of injury, classification systems, diagnostic approaches, and current treatment strategies for lower thoracic and lumbar spine fractures.